The Relationship Between Low Birth Weight Infants (BBLR) and the Development of Toddlers (1–3 Years) at Teungku Peukan Southwest Aceh Hospital in 2026 - Yeli Yusnita Sari; Cici Desnia Miranda; Riza Mustika (Athallah Publishing, 2026)
Background: Low Birth Weight Infants (LBWI) are still one of the health problems in various countries, including Indonesia. Babies with a birth weight of less than 2500 grams have a higher risk of impaired health, growth, and development. The toddler period is an important period in children's growth and development because there is rapid development in motor, language, and social aspects. Therefore, early developmental monitoring is very necessary, especially in children with a history of BBLR. Objective: This study aims to determine the relationship between low birth weight inf (BBLR) and the development of toddler children (1–3 years) at Teungku Peukan Southwest Aceh Hospital in 2026. Research Design: This study uses an analytical design with a cross sectional approach. The population is all toddler children (1-3 years old) who are examined at Teungku Peukan Southwest Aceh Hospital. The sampling technique used a total sampling with a sample of 36 respondents. Data analysis was carried out using the Chi-Square test. Results: The results showed that most children had normal birth weight and age-appropriate development. Statistical tests showed a p-value of < 0.05, which means that there is a significant relationship between BBLR and the development of toddlers. Conclusions: There is a significant relationship between BBLR and toddler (1–3 years) development. Suggestion: Health workers are expected to improve monitoring of growth and development and carry out early detection in children with a history of BBLR.